Thulium fiber laser lithotripsy: Is it living up to the hype? - John Denstedt; Fernanda C. Gabrigna Berto (Asian Journal of Urology)
Objective: The holmium:yttrium-aluminium-garnet laser (Ho:YAG) has been the gold standard for laser lithotripsy over the last three decades. After demonstrating good in vitro efficacy, the thulium fiber laser (TFL) has been recently released in the market and the initial clinical results are encouraging. This article aims to review the main technology differences between the Ho:YAG laser and the TFL, discuss the initial clinical results with the TFL as well as the optimal settings for TFL lithotripsy. Methods: We reviewed the literature focusing on the technological aspects of the Ho:YAG laser and TFL as well as the results of in vitro and in vivo studies comparing both technologies. Results: In vitro studies show a technical superiority of TFL compared to the Ho:YAG laser and encouraging results have been demonstrated in clinical practice. However, as TFL is a new technology, limited studies are currently available, and the optimal settings for lithotripsy are not yet established. Conclusion: TFL has the potential to be an alternative to the Ho:YAG laser, but more reports are still needed to determine the optimal laser for lithotripsy of urinary tract stones when considering all parameters including effectiveness, safety, and costs.